Analyzing Political Trends in the Blogosphere - Demartini, Gianluca; Siersdorfer, Stefan; Chelaru, Sergiu; Nejdl, Wolfgang (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
In the last years, the blogosphere has become a vital part of the web, covering a variety of different points of view and opinions on political and event-related topics such as immigration, election campaigns, or economic developments. Tracking the public opinion is usually done by conducting surveys resulting in significant costs both for interviewers and persons consulted. In this paper, we propose a method for extracting political trends in the blogosphere.To this end, we apply sentiment and time series analysis techniques in combination with aggregation methods on blog data to estimate the temporal development of opinions on politicians.